A Study on Mathematics Lesson Design of Prospective Elementary School Teachers by Using Latent Profile Analysis - Jin Sunwoo (Korea Society of Educational Studies in Mathematics, 2022)
Although interest in lesson design has been increasing among mathematics teachers, there is a lack of research on how to analyze the mathematics lesson design. Given this backgound, this study explored prior studies to extract four elements for analyzing lesson design and collected 104 lesson plans from prospective elementary school teachers in order to investigate their ability and characteristics of mathematics lesson designs. This study then analyzed their lesson plans by using Latent Profile Analysis (LPA) with four elements (i.e., understanding of mathematical tasks, considering students' mathematical thinking, connecting to mathematics content, and assessment). The results show that mathematics lesson plans designed by prospective elementary school teachers could be classified into three types: a lesson design that lacks understanding of learning goal and students' mathematical thinking, a lesson design that indicates superficial consideration of students' mathematical thinking, and a well-prepared lesson design with all of the elements. Based on the results, this study discusses the mathematics lesson designs of prospective elementary teachers as well as subsequent research.